Kafka : the decisive years - Stach, Reiner; Frisch, Shelley Laura (Princeton [N.J.] : Princeton University Press, 2013)
The acclaimed central volume of the definitive biography of Franz Kafka. Reiner Stach spent more than a decade working with over four thousand pages of journals, letters, and literary fragments, many never before available, to re-create the atmosphere in which Kafka lived and worked from 1910 to 1915, the most important and best-documented years of his life. This period, which would prove crucial to Kafka's writing and set the course for the rest of his life, saw him working with astonishing intensity on his most seminal writings-- The Trial, The Metamorphosis, The Man Who Disappeared (Amerika), and The Judgment. These are also the years of Kafka's fascination with Zionism; of his tumultuous engagement to Felice Bauer; and of the outbreak of World War I.
Prologue: The black star -- 1. At home with the Kafkas -- 2. Bachelors, young and old -- 3. Actors, Zionists, wild people -- 4. Literature and loneliness : Leipzig and Weimar -- 5. Last stop Jungborn -- 6. A young lady from Berlin -- 7. The ecstasy of beginning : "The Judgment" and "The Stoker" -- 8. A near defenestration -- 9. The girl, the lady, and the woman -- 10. Love and a longing for letters -- 11. Exultant weeks, little intrigues -- 12. The Bauer family -- 13. America and back : The Man Who Disappeared -- 14. The lives of metaphors : "The Metamorphosis" -- 15. The fear of going mad -- 16. Balkan war : the massacre next door -- 17. 1913 -- 18. The Man Who Disappeared : perfection and disintegration -- 19. Invention and exaggeration -- 20. Sexual trepidation and surrender -- 21. The working world : high tech and the ghosts of bureaucracy -- 22. The \proposal -- 23. Literature, nothing but literature -- 24. Three congresses in Vienna -- 25. Trieste, Venice, Verona, Riva -- 26. Grete Bloch : the messenger arrives -- 27. An all-time low -- 28. Kafka and Musil -- 29. Matrimonial plans and asceticism -- 30. Tribunal in Berlin -- 31. The Great War -- 32. Self-inflicted justice : The Trial and "In the Penal Colony" -- 33. The Return of the East -- 34. The grand disruption -- 35. No-man's-land.
Includes bibliographical references (pages 551-562) and index.
Translated from the German.
Print version record.
JSTOR
Keywords: Kafka, Franz, -- 1883-1924.; Kafka, Franz, -- 1883-1924.; Kafka, Franz; Kafka, Franz, -- 1883-1924; Authors, Austrian -- 20th century -- Biography; Écrivains autrichiens -- 20e siècle -- Biographies; BIOGRAPHY & AUTOBIOGRAPHY -- Literary; Authors, Austrian -- Biography. -- 20th century; Authors, Austrian; Judiska författare.; Tyskspråkiga författare.; Österrikiska författare.; Tjeckiska författare.; 1900-1999; collective biographies; Biographies; Biographies; Biographies